Suplementação proteico-energética para ovelhas em reprodução, gestação e lactação mantidas em pastos de capim-marandú - Kedma Leonora Silva Monteiro (2021)
The objective was to evaluate the supply of two levels of protein-energy supplementation to meet 15% and 30% of the nutritional requirements of sheep in different physiological stages, maintained in pastures. Two hundred and nine Texel F1 ewes were used, distributed in two treatments, by age, weight, order and type of farrowing, evaluated during three reproductive cycles in two years. The animals were kept in pastures of Brachiaria brizantha cv. Marandu throughout the experimental phase. There was no significant effect (P> 0.05) of supplementation on the weights of the sheep before and after the breeding season, in the breeding season and in the pre and postpartum period. Lambs' birth weight (BW) was influenced by sheep supplementation only in the first evaluation cycle, which comprises the beginning of the rainy season / beginning of the dry period, where the sheep that received the highest level of supplementation (30%) gave birth to lambs more weighed with 4.20 kg when compared to lambs from sheep with a lower supplementation level (15%) with an average birth weight of 3.62 kg. Supplementation levels did not significantly influence milk composition and production, the average total milk production was 1115.26 g / day. The provision of supplementation to meet 15% of the nutritional requirements in all categories of sheep breeders was enough to allow the performance and production of quality lambs, in addition to reducing the production costs of a breeding system in marandu grass pasture.